Efficacy of MUC1-targeted CAR-NK cells against human tongue squamous cell carcinoma - Lin, Xiaolan; Guan, Tian; Li, Yun; Lin, Yanchun; Huang, Guowei; Lin, Yan; Sun, Pingnan; Li, Congzhu; Gu, Jiang; Zeng, Haoyu; Ma, Changchun (Frontiers in Immunology, 2024)
The clinical efficacy of CAR-NK cells against CD19-expressing blood cancers has been demonstrated, and they have shown potential for treating solid tumors as well. However, the efficacy of CAR-NK cells for treating human oral tongue squamous cell carcinoma (OTSCC) has not been examined. We assessed MUC1 expression in human OTSCC tissue and a cell line using immunohistochemistry and immunofluorescence. We constructed NK cells that express CAR targeted to MUC1 from pluripotent stem cells (iPSC-derived MUC1-targeted CAR-NK cells) and evaluated their effectiveness against OTSCC in vitro using the xCELLigence Real-Time Cell Analysis system and CCK8 assay, and in vivo by measuring xenograft growth daily in BNDG mice treated with MUC1-targeted CAR-NK cells. As controls, we used iPSC-derived NK cells and NK-free media, which were CAR-free and blank, respectively. MUC1 expression was detected in 79.5% (66/83) of all OTSCC patients and 72.7% (24/33) of stage III and IV. In stage III and IV MUC1 positive OTSCC, 63.6% (21/33) and 48.5% (16/33) patients had a MUC1-positive cancer cell rate of more than 50% and 80%, respectively. The iPSC-derived MUC1-targeted CAR-NK cells exhibited significant cytotoxicity against MUC1-expressing OTSCC cells in vitro, in a time- and dose-dependent manner, and showed a significant inhibitory effect on xenograft growth compared to both the iPSC-derived NK cells and the blank controls. We observed no weight loss, severe hematological toxicity or NK cell-mediated death in the BNDG mice. The MUC1-targeted CAR-NK cells had significant efficacy against human OTSCC, and their promising therapeutic response warrants further clinical trials.